Implementing security in internet of things (IoT) - Tee, Ting Yi (2016)
Internet of Things (IoT) is the network of objects, or “things”, that are embedded with electronics that enables them to connect with each other, forming a large communication network for information transfer. Within the network, it is important to encrypt the data before transmission to achieve data security. Several factors must be taken into consideration when designing a security solution for IoT due to the fact that most of the embedded electronics involved in IoT are low-power processors or sensors that have limited resources. Several solutions for security in low-power processors is currently available online. This project focuses on studying and analysing one of the solutions used and optimizing the code to improve the performance on a low-power processor, namely the 8-bit ATMega328P processor present on an Arduino Uno board. In the end, it is determined that the encryption solution provided has been moderately optimized and the major bottleneck for the solution lies in the I/O component of the Arduino. A sample role of the microprocessor in a potential IoT implementation is then provided to visualize the potential use of the Arduino Uno in an IoT environment.